COMPARATIVE ANALYSIS OF DENTAL ASSISTING TECHNIQUES AND THEIR IMPACT ON PATIENT SATISFACTION IN SAUDI ARABIA - Hamad Mutlaq Aldhafeeri, Ali Sanad Halal Almutairi, Khalid Alhumaidi Rufaydan Almutairi, Hadyan Dhirbah Matar Almutairi, Nasser Lasaf Alanazi, Abdulaziz Mohammed Aldhafeeri (Chelonian Research Foundation, 2022)
Dental assisting plays a crucial role in the delivery of high-quality dental care and patient satisfaction. This study aims to compare different dental assisting techniques and evaluate their impact on patient satisfaction in Saudi Arabia. A mixed-methods approach was employed, involving a survey of 500 dental patients and semi-structured interviews with 20 dental assistants across various dental clinics in Saudi Arabia. The survey assessed patient satisfaction with different aspects of dental care, while the interviews explored dental assistants' perspectives on the techniques they use and their perceived impact on patient satisfaction. The findings revealed that patients were most satisfied with dental assistants who demonstrated empathy, clear communication, and efficient chairside assistance. Dental assistants who employed a patient-centered approach and utilized advanced technology reported higher levels of patient satisfaction. The study highlights the importance of integrating interpersonal skills training and technology-assisted techniques in dental assisting education and practice to enhance patient satisfaction in Saudi Arabia. Keywords: dental assisting, patient satisfaction, dental care, Saudi Arabia, mixed-methods